Pengaruh Self-Efficacy terhadap Kesiapan Kerja Mahasiswa Fakultas Ekonomi dan Manajemen IPB University - Aeni, Siti Tasya Octa; Rahmawati, Siti (JUDICIOUS, 2023)
Faculty of Economics and Management is one of the faculties at IPB University, Dramaga, Bogor. Faculty of Economics and Management (FEM) IPB University has an average waiting period for work > 6 months higher than the IPB University average. Work readiness is something that students must have, one of the factors that affect work readiness is self-efficacy. Therefore, this study aims to analyze the effect of self-efficay on the work readiness of students of the Faculty of Economics and Management. The research data were obtained from primary data and secondary data from filling out questionnaires by FEM IPB University students in 2020, journals, books, and sources. The study used simple linear analysis. The results of this study indicate that self-efficacy affects student work readiness with a correlation value of 42.5%..